Hyperstimulation Syndrome of the Ovary: A review on clinical feature, pathophysiology, risk factors, and prevention. - Abbas Ali, Rihab; Abbood Mukheef, Maher; Hadi Majeed, Hind (Karbala Journal of Medicine, 2022)
Hyperstimulation syndrome of the ovary is a dangerous complication of ovulation induction during infertility treatment by gonadotropins stimulation and human chorionic gonadotropin injection. Increased capillary permeability, causing fluid leakage from the intravascular compartment, with the accumulation of fluid in the third-space and consequent intravascular dehydration, is the main change in the pathophysiology of Hyperstimulation syndrome of the ovary. Vascular endothelial growth factor (VEGF) is the main mediator in the development of Hyperstimulation syndrome of the ovary. The recent application of new modalities: GnRH antagonist protocol, GnRH agonist (GnRHa) triggering of ovulation and embryo/oocyte vitrification, facilitates the elimination of Hyperstimulation syndrome of the ovary associated with controlled control ovarian hyperstimulation(COH) for IVF program. In this manuscript, we reviewed the pathophysiology, clinical features, predisposing factors, and both primary and secondary arrangement for preventing Hyperstimulation syndrome of the ovary as there is no single measure to prevent OHSS totally. Therefore, categorizing the women based on their risk potentiality seems to be beneficial to direct the line of management as early as possible to avoid the emergence of Hyperstimulation syndrome of the ovary.